2020
DOI: 10.1155/2020/2563208
|View full text |Cite
|
Sign up to set email alerts
|

Association of JMJD2B and Hypoxia-Inducible Factor 1 Expressions with Poor Prognosis in Osteosarcoma

Abstract: Background. JMJD2B has been reported to be implicated in malignant tumors. This study is aimed at exploring the expression and prognostic significance of JMJD2B in osteosarcoma and its association with hypoxia-inducible factor 1 (HIF1). Methods. The histopathological and clinical characteristics were retrospectively reviewed from 53 osteosarcoma patients. JMJD2B and HIF1 were examined by immunohistochemical staining of paraffin-embedded osteosarcoma samples, and their association with clinical characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…IHC staining was performed using a previously described protocol. 31 , 32 The staining intensity was evaluated as follows: 0, no staining; 1, beige; 2, darker beige; and 3, tan. The staining extent was scored as follows: 0, 0% stained; 1, 1% to 25% stained; 2, 26% to 50% stained; and 3, 51% to 100% stained.…”
Section: Methodsmentioning
confidence: 99%
“…IHC staining was performed using a previously described protocol. 31 , 32 The staining intensity was evaluated as follows: 0, no staining; 1, beige; 2, darker beige; and 3, tan. The staining extent was scored as follows: 0, 0% stained; 1, 1% to 25% stained; 2, 26% to 50% stained; and 3, 51% to 100% stained.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, higher KDM6A and KDM6B expression is reportedly associated with greater H3K27me3 demethylation in human OS tissue and different OS cell lines 16 . In another study that examined IHC-stained OS tissue samples from 53 patients, higher KDM4B levels were positively associated with shorter OS survival as well as OS progression, as determined by higher Enneking staging results, a higher likelihood of distant metastases and poor differentiation on histology 24 . KDM4C silencing has been shown to increase H3K9me3 levels in MG63 and SaOS-2 human OS cells 25 .…”
Section: Discussionmentioning
confidence: 98%
“…Hypoxic environments occur in many solid tumors, including OS, and can trigger the release of hypoxia-inducible factors HIF-1α, HIF-2α, and HIF-3α, which modulate EMT master regulators such as SNAIL and TWIST to promote EMT and CSC progression 26 27 28 . In OS, HIF-3α overexpression in hypoxic conditions can activate KDM3A to decrease H3K9me2 levels at the SOX9 mRNA promoter region, leading to greater OS proliferation and invasion while restricting apoptosis 26 , while another study has found that higher levels of KDM4B and HIF-1α are associated with worse OS prognosis and progression to metastatic disease 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Lysine demethylase 4 (KDM4) subfamily H3K9 histone demethylases, as epigenetic regulators, are mainly responsible for the demethylation of histones H3K9 and H3K36 to influence chromosome structure and modulate gene expression [49] , resulting in a pivotal function in cell differentiation, development and death, and are involved in the study of diverse cancer prognosis and mechanisms including OS [50] , [51] . Chen et al clarified that deletion of KDM4A induced ferroptosis in OS cells by applying different forms of cell death inhibitors.…”
Section: Potential Mechanisms Underlying Ferroptosis In Osteosarcomamentioning
confidence: 99%